Why Do Young City Women Disobey the Protocols During the Covid-19 Pandemic? - Nurlina Subair; Risma Haris (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to determine the attitudes and responses of women in urban areas in complying with protocols to prevent the spread of the coronavirus in Indonesia. Conducted this research with a descriptive survey research method; the sample in this study was young women in Makassar city. Data collection techniques using interviews and questionnaires. The results of the study show (1) The effectiveness of the implementation of the Covid-19 control and prevention program has been implemented. However, some young women still have not implemented it, even around 49% who have not implemented the program, namely wearing masks if they experience respiratory symptoms. Meanwhile, (2 The sociodemographic relationship with Covid-19 control and prevention policies, specifically the use of medical masks, shows that the average age who routinely applies them is young city women aged 12-18 years, while city women aged 19-25 years are lower in the application of medical masks